Legal Perspective on Effectiveness of Pre-Work Cards for Indonesian People - Najella Zubaidi; Regy Gusti Pratama; Sholahuddin Al-Fatih (BESTUUR, 2020)
Many populations in Indonesia have made various problems that arise one of the problems of unemployment that occur in Indonesia. Many unemployment certainly makes the Indonesian economy decline, of course it becomes the duty of the government in overcoming the decline in the Indonesian economy and the issue of unemployment which is surged annually especially in the year 2020. Indonesian President Joko Widodo has created a pre-work card program which is expected to suppress the unemployment rate in Indonesia. With community pre-work cards can increase productivity and competitiveness of work and improve work competence. The community who participated in the pre-employment card program will be provided with training and incentives during the pre-work card training. But the government itself does not guarantee after joining the pre-employment program, people will get a job or not. Of course again this is a government task to be able to open extensive jobs for the people of Indonesia but this also needs to get support and participation from the people of Indonesia to make this pre-work card a successful program and can suppress the unemployment rate in Indonesia.  Keywords: Pre Work Cards; Unemployment; Effectiveness.